Understanding Participations in The Design Development of Jumputan Micro Small Medium-sized Enterprises in Palembang, Indonesia - Puspita, Eka Arifianty (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2025)
Effective participation in the design process is projected to provide better outcomes in the development program of Micro, Small, and Medium-sized Enterprises (MSMEs). Allowing all parties impacted by the development program to engage properly in the process will provide relevant improvement and offer sustainability.Given the imperative of determining suitable participation, this research delves into the forms of participation that arise during the design process using Yanki Lee's theory. This theory classifies participation according to four objectives: innovation, collaboration, emancipation, and motivation. In regard to the study, the design development, particularly using the Transforming Tradition design model, served for two MSMEs in Palembang, South Sumatra, were analyzed to determine the type of participation that arose during the design process. While the design process successfully produced a series of designs for both MSMEs, the research discovered an interconnection between the types of roles, relationships, and interactions that each actors possesses, influence the diverse mode of participation. The research also reveals that an actor's capacity and interest to participate in the design process define their role of participation, which is primarily responsible for determining the dynamics of participation in a development program are optimized.